Nutritive values and phytochemical compositions of edible indigenous plants in Thailand - Sridonpai, Piyanut; Kongprapun, Pichakorn; Sungayuth, Nongnuch; Sukprasansap, Monruedee; Chimkerd, Chanika; Judprasong, Kunchit (Frontiers in Sustainable Food Systems, 2022)
Indigenous edible plants are important components of food systems that are linked to food security and are important sources of nutrients with potential health benefits. Since knowledge about Thailand’s various indigenous plants is limited, this study determined the nutritive values and bioactive compounds contained in eight edible indigenous plants growing within the conservation area of the Electricity Generating Authority of Thailand, Srinakarind Dam, Kanchanaburi province. Plant samples were analyzed as fresh or cooked (blanched or boiled) depending on customary preparation and consumption habits. Results showed that shoots and young leaves of Jang (Maerua siamensis Kurz), Ta-Kuk (Albizia lebbeck (L.) Benth), Pak-Wan-Pa (Melientha suavis Pierre), and Som-kob (Hymenodictyon exelsum Wall.) have potential health benefits in terms of nutritive values (vitamin C, dietary fiber, protein) and bioactive compounds (carotenoids, phenolic compounds, antioxidant activity). Shoots and young leaves of Jang were highest in protein, dietary fiber, phenolic compounds, and antioxidant activity. Shoots and young leaves of Ta-Kuk had the highest vitamin C level and considerable amounts of protein, dietary fiber, phenolic compounds, antioxidant activity, and carotenoids. Loss of vitamin C and bioactive compounds occurred most often in boiled plants rather than those that were blanched, though carotenoids increased with either boiling or blanching. This study’s important findings should be translated into practical knowledge and disseminated to local communities and at the national level to encourage plant conservation, nutrition education, and the increased consumption of these indigenous plants.